Psyren. 10, Alien sky - Iwashiro, Toshiaki, 1977- (Shonen Jump manga., 2013)
Nemesis Q's creator reveals the true purpose of the Psyren game, and Hiryu and Oboro get left behind while Ageha, Amamiya, and Kabuto return home without them.